(untitled) (Journal of Plant Disease Sciences, 2025)
Linseed suffers significant grain yield losses due to various abiotic and biotic stress factors, with powdery mildew caused by Oidium lini (Skoric) being one of the most critical biotic threats. This disease reduces photosynthetic efficiency and grain yield, manifesting in symptoms such as drooping and yellowing of leaves, reduced capsule number, and smaller seed size. To address this, a study was conducted from 2019–2020 to 2021–2022 to evaluate the effectiveness of defence inducers and a fungicide in managing powdery mildew.The treatments included salicylic acid (50 and 100 ppm), monopotassium phosphate (1%), sodium propionate (1%), and hexaconazole (0.1%). Among these, seed treatment followed by foliar application of salicylic acid at 50 ppm at 30 and 45 days after sowing (DAS) showed the highest disease reduction (34.99%), maximum seed yield (1219 kg/ha), and the highest incremental cost-benefit ratio (ICBR) of 1:6.71.These findings underscore the potential of systemic acquired resistance (SAR) and induced systemic resistance (ISR)-based inducers as eco-friendly alternatives to conventional fungicides in the sustainable management of powdery mildew in linseed.